2022
DOI: 10.1002/mds.28976
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Salivary Real‐Time Quaking‐Induced Conversion in Parkinson's Disease and Multiple System Atrophy

Abstract: Background Aggregation of α‐synuclein (oligomeric α‐syn) has been considered as the pathological hallmark of Parkinson's disease (PD) and multiple system atrophy (MSA). Studies showed oligomeric α‐syn/total α‐syn ratio was increased in the saliva of patients with PD, suggesting that seeding activity of salivary oligomeric α‐syn may be a novel biomarker for the diagnosis of PD and MSA. Objective This study aimed to evaluate the diagnostic value of salivary α‐syn seeding activity in patients with PD and MSA. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…To date, only one study is available, reporting the diagnostic accuracy of α-syn SAAs in saliva samples collected from patients with PD and MSA. 38 In this work, SAAs produced good results in discriminating PD and MSA from controls (PD: sens 76% and spec 94.4%; MSA: sens 61.1% and spec 94.4%).…”
Section: α-Syn Saas In Easily Accessible Biological Matricesmentioning
confidence: 58%
See 1 more Smart Citation
“…To date, only one study is available, reporting the diagnostic accuracy of α-syn SAAs in saliva samples collected from patients with PD and MSA. 38 In this work, SAAs produced good results in discriminating PD and MSA from controls (PD: sens 76% and spec 94.4%; MSA: sens 61.1% and spec 94.4%).…”
Section: α-Syn Saas In Easily Accessible Biological Matricesmentioning
confidence: 58%
“…A significantly different seeding activity has been observed also in saliva from patients with MSA and PD, able to differentiate the 2 disorders with 61% sensitivity and 94% specificity (Table 3). 38…”
Section: α-Synuclein Saasmentioning
confidence: 99%
“…Interestingly in prodromal DLB 5/5 nasal brushing samples seeded positive reactions (Perra et al, 2021 ), which seems more promising than the Stefani et al ( 2021 ) study on iRBD, albeit with more limited numbers and a different prodromal phenotype. Very recently, RT-QuIC on saliva has demonstrated 76% sensitivity in distinguishing clinically diagnosed PD patients (57/75 positive) and 61.1% sensitivity in distinguishing clinically diagnosed MSA patients (11/18 positive) from non-neurodegenerative healthy controls, with 94.4% specificity (34/36 controls testing negative; Luan et al, 2022 ). In all of these studies, relatively low numbers and a lack of neuropathological confirmation of clinical diagnosis are limitations.…”
Section: Role Of Protein Aggregation With Seed Amplification Assays I...mentioning
confidence: 99%
“…Subsequently, multiple teams have observed high specificity and sensitivity of α-Syn RT-QuIC in CSF and brain tissue ( Groveman et al, 2018 ; Sano et al, 2018 ; Bongianni et al, 2019 ; Garrido et al, 2019 ; Kang et al, 2019 ; van Rumund et al, 2019 ; Han et al, 2020 ; Rossi et al, 2020 ; Bargar et al, 2021b ; Brockmann et al, 2021 ; Iranzo et al, 2021 ; Perra et al, 2021 ; Poggiolini et al, 2021 ). Recent studies applied RT-QuIC to submandibular gland, biopsies of skin, and olfactory mucosa, which indicates a growing trend toward non-invasive testing ( De Luca et al, 2019 ; Manne et al, 2020a , b ; Wang et al, 2020 ; Bargar et al, 2021a ; Kuzkina et al, 2021 ; Stefani et al, 2021 ; Luan et al, 2022 ). The results of protease resistance of RT-QuIC products showed that seeded fibrils had obvious disease-specific protease sensitivity in PD and MSA, indicating that RT-QuIC amplification could preserve the structural features of the initial seeds and help to differentiate between different strains ( Manne et al, 2020b ).…”
Section: Techniques Available To Detect α-Syn Seedingmentioning
confidence: 99%